2020
DOI: 10.9734/ajrid/2020/v4i330149
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity of Human Immunodeficiency Virus among Intending Blood Donors in Rivers State, Nigeria

Abstract: Aims: Provision of constant and safe blood has been a public health challenge in Sub-Saharan Africa with a high prevalence of transfusion-transmissible infections (TTIs). This study aimed at determining the seroprevalence of the Human Immunodeficiency Virus (HIV) among prospective blood donors at two Hospitals (government and private-owned) in Rivers State, and also to relate some demographic studies to the screening results. Study Design:  Cross-sectional study. Place and Duration of Study: Two Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 12 publications
(15 reference statements)
3
6
2
Order By: Relevance
“…These most recent findings were consistent with our earlier research in Ibadan, Nigeria (Okonko et al, 2012), which found a higher frequency in people over 40. This observation, however, differs from studies we conducted in Port Harcourt (Abeni et al, 2020) and Ugheli, Delta State, Nigeria (Ogbodo et al, 2015), which found greater prevalences in the age group >26 years.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These most recent findings were consistent with our earlier research in Ibadan, Nigeria (Okonko et al, 2012), which found a higher frequency in people over 40. This observation, however, differs from studies we conducted in Port Harcourt (Abeni et al, 2020) and Ugheli, Delta State, Nigeria (Ogbodo et al, 2015), which found greater prevalences in the age group >26 years.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence rate of 5.6% obtained from this study is comparable to the prevalence rate of 5.20% that was reported in Ghana (Acquaye & Tettey-Donkor, 2000). It is also comparable to the 5.70% reported in Jos, Nigeria (Inyama et al, 2005), the 5.0% reported in Port Harcourt, Nigeria (Abeni et al, 2020) and the 6.1% and 6.0% reported by Dammulak et al (2013) in Jos and Buseri et al (2009) in Osogbo, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations